2019
DOI: 10.1111/jcmm.14915
|View full text |Cite
|
Sign up to set email alerts
|

Imperatorin promotes osteogenesis and suppresses osteoclast by activating AKT/GSK3 β/β‐catenin pathways

Abstract: Osteoporosis is caused by disturbance in the dynamic balance of bone remodelling, a physiological process, vital for maintenance of healthy bone tissue in adult humans. In this process, a new bone is formed by osteoblasts and the pre‐existing bone matrix is resorbed by osteoclasts. Imperatorin, a widely available and inexpensive plant extract with antioxidative and apoptotic effects, is reported to treat osteoporosis. However, the underlying mechanism and specific effects on bone metabolism have not been eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…FGF19 and its receptor FGFR4 are oncogenic drivers of liver cancer and associated with a poor prognosis [ 35 ]. CTNNB1 is generally considered as an intermediate regulator molecule of the FGF19-FGFR4 signaling pathway [ 28 , 36 , 37 , 38 ]. In addition, a lot of studies have shown that the downregulation of CTNNB1 was associated with the downregulations of CDH2, ALCAM and ICAM1, which is consistent with our results [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…FGF19 and its receptor FGFR4 are oncogenic drivers of liver cancer and associated with a poor prognosis [ 35 ]. CTNNB1 is generally considered as an intermediate regulator molecule of the FGF19-FGFR4 signaling pathway [ 28 , 36 , 37 , 38 ]. In addition, a lot of studies have shown that the downregulation of CTNNB1 was associated with the downregulations of CDH2, ALCAM and ICAM1, which is consistent with our results [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…This means that various physiological functions of type-H endothelial cells can be adopted as potential pharmacological activities of calcitonin family peptides, targeting bone defects, osteoporosis, and even bone metastasis (Singh et al, 2019). Moreover, the present exploration of the AKT-and NF-κB-mediated accumulation and activation of βcatenin not only supplements the mechanisms by which ADM2 and other calcitonin family peptides may potentially regulate osteogenesis and angiogenesis, but also provide novel insights into the relationship between calcitonin family peptides and osteoclastogenesis, except for the cAMP pathway, according to the inhibitory effect of β-catenin signaling on osteoclastogenesis (Yan et al, 2020).…”
Section: Discussionmentioning
confidence: 82%
“…Subsequently, we investigated if the PKC/Akt axis modulates the canonical Wnt signaling pathway. Since GSK3β can be phosphorylated at Ser9 and thus be inactivated by Akt, and—when active—modulate canonical Wnt signaling by promoting the degradation of β-catenin [ 25 ], we first examined the connection between GSK3β phosphorylation and Akt activity in DFCs (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, both PKC and Akt are known to interact with the nuclear factor “kappa-light-chain-enhancer” of activated B cells (NF-κB) signaling pathway [ 21 , 22 ], which was shown to regulate the osteogenic differentiation in dental pulp stem cells [ 23 , 24 ]. Another downstream target of Akt is the canonical Wnt signaling pathway as Akt promotes osteogenesis in rat mesenchymal stem cells by phosphorylation of glycogen synthase kinase 3β (GSK3β), which regulates the activity of β-catenin [ 25 ]. The canonical Wnt signaling pathway is also involved in the osteogenic differentiation of human DFCs, albeit with an inhibitory impact [ 26 ].…”
Section: Introductionmentioning
confidence: 99%